Atmospheric Heating Events Associated with Fine-scale Flux Emergence in Ephemeral Regions - Yang, Hanlin; Wang, Jingxiu; Jin, Chunlan (The Astrophysical journal, 2025)
Coronal heating has puzzled solar physicists for decades. The question of why the Sun’s upper atmosphere is significantly hotter than its lower atmosphere remains a key mystery. It is commonly believed that the source of coronal heating comes from the Sun’s magnetic field, and more complex magnetic dynamics are more efficient in heating. In an earlier work, we studied the secondary (or finer-scale) flux emergence identified in five ephemeral regions (ERs), selected during the last solar minimum. Here we further explore the atmospheric response to the secondary flux emergences (SFEs) that were identified in the first paper. We further reveal that approximately 80% of the 172 identified SFEs are associated with atmospheric heating events. The heating is most likely associated with magnetic reconnection involving the SFE. Overall, a solar quiet region is heated by several hundred thousand degrees during the flux emergence of an ER.